2016
DOI: 10.1111/bju.13515
|View full text |Cite
|
Sign up to set email alerts
|

Mirabegron causes relaxation of human and rat corpus cavernosum: could it be a potential therapy for erectile dysfunction?

Abstract: ObjectiveTo examine the effects of mirabegron, a selective b 3 -adrenoceptor agonist that has recently been approved for the treatment of overactive bladder (OAB), on erectile function. Stimulation of b 3 -adrenoceptors localised in cavernosal smooth muscle cells may play a physiological role in mediating penile erection, and offer a beneficial pharmacological action for patients who have OAB and erectile dysfunction (ED). Materials and MethodsCorpus cavernosal (CC) specimens were obtained from patients with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…In addition, a marked alteration in basal ICP was observed in diabetic rats after intracavernosal injection of mirabegron. However, our previous data showed that intracavernosal injection of mirabegron (doses of 0.1-1 mg/kg) had a minor effect on in vivo erectile response [6]. Interestingly, mirabegron did not increase ICP basal levels in healthy rats.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In addition, a marked alteration in basal ICP was observed in diabetic rats after intracavernosal injection of mirabegron. However, our previous data showed that intracavernosal injection of mirabegron (doses of 0.1-1 mg/kg) had a minor effect on in vivo erectile response [6]. Interestingly, mirabegron did not increase ICP basal levels in healthy rats.…”
Section: Discussionmentioning
confidence: 83%
“…The CN was stimulated (2.5, 5 and 7.5 V, 15 Hz, 30-second pulse width) with a square pulse stimulator (Grass Instruments, Quincy, MA) and, ICP and MAP were continuously measured. The measurements were repeated after intracavernosal administration of mirabegron (dose of 0.4 mg/kg) in the diabetic group [6,13]. All injections of mirabegron solution (10 − 2 M) were administered in a total volume of 300 µL, and a washout period of 15-30 min was observed between injections.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Saline Treatment * While studies on the relaxatory effects of mirabegron in human and rat corpus cavernosum or human and rabbit prostate could not show any mechanistic involvement of NO, 23,24 others have suggested that NO is part of the relaxatory mechanism of mirabegron in the bladder. 11 The current study shows that combination treatment causes release of NO in the urinary bladder.…”
Section: Volume/micturition (Ml)mentioning
confidence: 99%